2006
DOI: 10.1093/aob/mcl039
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation and Relationships of Populations in the Cycas balansae Complex (Cycadaceae) and its Conservation Implications

Abstract: ISSR data suggest that the C. balansae complex has evolved into five genetically distinct units. These might be derived from a relatively widespread common ancestor through multiple vicariant events including geographical isolation resulting from the collision of the Indian plate with the Eurasian plate and from Pleistocene glaciations. In conservation, attention should be paid to each genetic unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…100 species, mainly Australian and Indo-Chinese extending as far as East Africa. In Cibrián-Jaramillo et al 7 we showed that allelic richness does not suggest a "genetic or evolutionary relict," 8 [2][3][4][5][6] Our results from Cycas micronesica in Guam 7 and sister species (Cibrián-Jaramillo A, et al unpublished) support this notion.…”
Section: Introductionsupporting
confidence: 60%
“…100 species, mainly Australian and Indo-Chinese extending as far as East Africa. In Cibrián-Jaramillo et al 7 we showed that allelic richness does not suggest a "genetic or evolutionary relict," 8 [2][3][4][5][6] Our results from Cycas micronesica in Guam 7 and sister species (Cibrián-Jaramillo A, et al unpublished) support this notion.…”
Section: Introductionsupporting
confidence: 60%
“…Population genetics theory predicts that genetic variation in small and isolated populations will erode over time (mostly due to genetic drift), resulting in an isolation‐by‐distance pattern where individuals at closer geographic distance will have higher chances of being identical by descent (Slatkin 1993; Hedrick 2000; Rousset 2000) . Indeed, with only a few exceptions (Xiao & Gong 2006) most cycad species have a highly structured distribution of low genetic variation, with low levels of gene flow and a pattern of isolation by distance even at small geographic distances (Ellstrand et al. 1990; Walters & Decker‐Walters 1991; Yang & Meerow 1996; Sharma et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, available seed dispersal distance information seems more than any other ecological process in Xishuangbanna. Most of the seeds are reported to travel a short distance to other places within approximately 1 km (Tang et al, 2008;Zhou et al, 2007), while others have long dispersal distances to as much as 2-7 km, though this rarely occurs (Xiao and Gong, 2006). Without additional research related to seed dispersal by large mammals, the long-distance seed dispersals in Xishuangbanna may exist but are rarely studied as compared with the discovery of 5-12 km seed dispersal distances by elephants in other parts of world (Theuerkauf et al, 2000).…”
Section: Resource Patch Selection and Fragmentation Effect Quantificamentioning
confidence: 99%